Perkembangan Sosial ekonomi masyarakat transmigrasi desa perintis di rimbo bujang tahun 1975-2020 - Dian Purnamasari; Rusdi Rusdi (Jurusan Sejarah FIS UNP, 2021)
This writing aims to analyze the reasons and developments of the socio-economic life of the transmigration community in the Pioneer Village in Rimbo Bujang. The focus of the study is on the development of the socio-economic life of the transmigration community in the Perintis Village in 1975 – 2020. The importance of this research is because the transmigration of the community from Java to the Pioneer Village has had a very rapid impact on regional expansion, regional development, social and economic development in Rimbo. single. The technique used in this task is a historical research technique that includes four stages such as histography, interpretation, source criticism and heuristics. Based on the results of the initial research, the arrival of the transmigration community in the Pioneer Village came from Yogyakarta. The reason the Javanese people took part in transmigration in 1975 was to look for more land because the land in Java was very narrow while the population was getting denser, the economy was difficult so following transmigration wanted to change their lives and the economy for the better in the future. The social change of the Pioneer Village community which started from people who do not have permanent jobs to have oil palm plantations, rubber and transmigration houses and in terms of education, many Pioneer Village children have started going to school. The pioneering village community also has several other social activities such as recitation, mutual cooperation, farmer communities, etc. From an economic point of view, from year to year, income is increasing because the 5 hectares of agricultural produce from the government has started to produce both once a month and every 2 weeks and people's livelihoods have started to vary, not only farming, such as entrepreneurs, civil servants, employees. private etc. keyword: development, transmigration, social economi